New user? Sign up

Existing user? Sign in

\[ \large \lim_{x\to\frac13} \dfrac{\sqrt3 - \tan(\pi x)}{3x-1} = \ ? \]

Note by A K 2 years, 1 month ago

Sort by:

We could just use L'Hopital's rule, but I'm assuming that you are looking for an approach that does not use this rule.

Let \(u = x - \dfrac{1}{3}.\) Then \(u \rightarrow 0\) as \(x \rightarrow \dfrac{1}{3}\) and \(x = u + \dfrac{1}{3},\) in which case

\(\sqrt{3} - \tan(\pi x) = \sqrt{3} - \tan\left(\pi u + \dfrac{\pi}{3}\right) = \sqrt{3} - \dfrac{\tan(\pi u) + \tan(\frac{\pi}{3})}{1 - \tan(\pi u)\tan(\frac{\pi}{3})} =\)

\(\sqrt{3} - \dfrac{\tan(\pi u) + \sqrt{3}}{1 - \sqrt{3}\tan(\pi u)} = \dfrac{\sqrt{3} - 3\tan(\pi u) - \tan(\pi u) - \sqrt{3}}{1 - \sqrt{3}\tan(\pi u)} = \dfrac{-4\tan(\pi u)}{1 - \sqrt{3}\tan(\pi u)}.\)

Thus the original limit can be written as

\(\lim_{u \rightarrow 0} \dfrac{-4\tan(\pi u)}{3u*(1 - \sqrt{3}\tan(\pi u))} =\)

\(\lim_{u \rightarrow 0} \dfrac{-4\pi \tan(\pi u)}{3*(\pi u)} * \lim_{u \rightarrow 0} \dfrac{1}{1 - \sqrt{3}\tan(\pi u)} = -\dfrac{4\pi}{3} * \lim_{w \rightarrow 0} \dfrac{\tan(w)}{w} * 1 = \boxed{-\dfrac{4 \pi}{3}},\)

where \(w = \pi u \rightarrow 0\) as \(u \rightarrow 0.\) Note also that \((1 - \sqrt{3}\tan(\pi u)) \rightarrow 1\) as \(u \rightarrow 0.\)

Log in to reply

Nice! Approaches without using L'hopital's rule are always really good.

Thanks! L'Hopital's is really useful if you want a quick result, but I like the challenge of trying to find an alternative approach. :)

@Brian Charlesworth – Another way is to put \( \pi x = y \) and by first principles we can say the limit equals negative of the derivative of \( \tan y \) at \( y = \dfrac{ \pi}{3} \). This is similar to L'Hospital but not completely.

-4π/3

\(\frac{-4\pi}{3}\)

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestWe could just use L'Hopital's rule, but I'm assuming that you are looking for an approach that does not use this rule.

Let \(u = x - \dfrac{1}{3}.\) Then \(u \rightarrow 0\) as \(x \rightarrow \dfrac{1}{3}\) and \(x = u + \dfrac{1}{3},\) in which case

\(\sqrt{3} - \tan(\pi x) = \sqrt{3} - \tan\left(\pi u + \dfrac{\pi}{3}\right) = \sqrt{3} - \dfrac{\tan(\pi u) + \tan(\frac{\pi}{3})}{1 - \tan(\pi u)\tan(\frac{\pi}{3})} =\)

\(\sqrt{3} - \dfrac{\tan(\pi u) + \sqrt{3}}{1 - \sqrt{3}\tan(\pi u)} = \dfrac{\sqrt{3} - 3\tan(\pi u) - \tan(\pi u) - \sqrt{3}}{1 - \sqrt{3}\tan(\pi u)} = \dfrac{-4\tan(\pi u)}{1 - \sqrt{3}\tan(\pi u)}.\)

Thus the original limit can be written as

\(\lim_{u \rightarrow 0} \dfrac{-4\tan(\pi u)}{3u*(1 - \sqrt{3}\tan(\pi u))} =\)

\(\lim_{u \rightarrow 0} \dfrac{-4\pi \tan(\pi u)}{3*(\pi u)} * \lim_{u \rightarrow 0} \dfrac{1}{1 - \sqrt{3}\tan(\pi u)} = -\dfrac{4\pi}{3} * \lim_{w \rightarrow 0} \dfrac{\tan(w)}{w} * 1 = \boxed{-\dfrac{4 \pi}{3}},\)

where \(w = \pi u \rightarrow 0\) as \(u \rightarrow 0.\) Note also that \((1 - \sqrt{3}\tan(\pi u)) \rightarrow 1\) as \(u \rightarrow 0.\)

Log in to reply

Nice! Approaches without using L'hopital's rule are always really good.

Log in to reply

Thanks! L'Hopital's is really useful if you want a quick result, but I like the challenge of trying to find an alternative approach. :)

Log in to reply

Log in to reply

-4π/3

Log in to reply

\(\frac{-4\pi}{3}\)

Log in to reply